2018
DOI: 10.1159/000487357
|View full text |Cite
|
Sign up to set email alerts
|

The Placental Secretome: Identifying Potential Cross-Talk Between Placenta and Islet β-Cells

Abstract: Background/Aims: Insulin-secreting islet β-cells adapt to the insulin resistance associated with pregnancy by increasing functional β-cell mass, but the placental signals involved in this process are not well defined. In the current study, we analysed expression of G-protein coupled receptor (GPCR) mRNAs in mouse islets and islet GPCR ligand mRNAs in placenta during pregnancy to generate an atlas of potential interactions between the placenta and β-cells to inform future functional studies of islet adaptive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…qRT-PCR measurements demonstrated that mRNAs for Crh, Ucn1, Ucn2 and Ucn3 were all expressed by mouse placenta at day 18 at similar levels (Fig. 3A), confirming our previous observations (Drynda et al 2018). Furthermore, all four peptides were detected in the peripheral circulation, with UCN2 being the most abundant circulating CRHR agonist (Fig.…”
Section: Circulating Crh and Urocortin Profile During Pregnancysupporting
confidence: 89%
See 2 more Smart Citations
“…qRT-PCR measurements demonstrated that mRNAs for Crh, Ucn1, Ucn2 and Ucn3 were all expressed by mouse placenta at day 18 at similar levels (Fig. 3A), confirming our previous observations (Drynda et al 2018). Furthermore, all four peptides were detected in the peripheral circulation, with UCN2 being the most abundant circulating CRHR agonist (Fig.…”
Section: Circulating Crh and Urocortin Profile During Pregnancysupporting
confidence: 89%
“…Isolated female islets from non-pregnant and pregnant (day 16) mice were immediately snap frozen in liquid nitrogen following purification from the exocrine pancreas for subsequent RNA extraction using RNeasy Mini Kit (Qiagen) and High-Capacity cDNA Reverse Transcription Kit (Applied Biosystems) for cDNA synthesis, as described previously (Drynda et al 2018). Placenta samples were also collected after termination at day 18 of pregnancy and snap frozen.…”
Section: Quantification Of Mrna Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of the pancreatic β-cell, recent research has identified putative pathways for placental crosstalk with the islet in mice [ 62 ]. More specifically, ligands for G-protein coupled receptors that, independent of lactogens, are part of the placental secretome and may be involved in pregnancy-induced adaptive expansion in islets [ 62 ].…”
Section: Placental Signalling and Metabolismmentioning
confidence: 99%
“…In the context of the pancreatic β-cell, recent research has identified putative pathways for placental crosstalk with the islet in mice [ 62 ]. More specifically, ligands for G-protein coupled receptors that, independent of lactogens, are part of the placental secretome and may be involved in pregnancy-induced adaptive expansion in islets [ 62 ]. Corticotrophin releasing hormone (CRH) receptor was shown to be elevated mid-gestation in islets, and CRH expression was increased at the same time in the placenta; CRH has been shown to mediate insulin secretion [ 63 ] and β-cell proliferation [ 64 ] and could be an important mediator of β-cell adaptation potentially stimulated by placental signalling.…”
Section: Placental Signalling and Metabolismmentioning
confidence: 99%